Odpis memoriału złożonego premierowi rządu RP oraz ministrom przez powiatowy komitet osiedleńczy w Kwidzynie z 1 października 1945 roku = A copy of Kwidzyn local settlement committee`s memorial addressed to polish prime minister and ministers from october 1, 1945 - Łukianow, Małgorzata; Maciejewski, Marcin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Presented memorial addressed to government in Warsaw is an interesting source, depicting not only issues related to the process of settlement in Kwidzyn, but also recent history of this city since it`s annexation to Poland. It can be also considered a part of the wider context, of Polish Western and Northern Territories. The memorial illustrates the attitude of local government and the mindset of it?s members towards the idea of development and polonization of aforementioned territories.
Keywords: Kwidzyn; Ziemie Zachodnie i Północne; Osadnictwo; powiatowy komitet osiedleńczy; post-war settlement; Polish Western and Northern Territories; Polish Recovered Territories; local settlement comittee